The legal study on unregistered marriages in Malaysia / Nur Taskin Omar ...[et al.] - Omar, Nur Taskin; Mohd. Jamali, Nabila Huda; Mohd. Hanafi, Nurul Hidayah; Hasnul, Syarmeen Amira (2011)
After the Law Reform (marriage & Divorce) Act 1976 came into force in the year of 1982, registration of marriage has been made compulsory for the local non-Muslim couples. However, section 34 became a problematic section as it provides otherwise, consequently suggesting that registration of marriage is actually mere procedural and not compulsory. Therefore, this study examines the importance of requirement of registration of marriage under the Law Reform (Marriage & Divorce) Act 1976 and the consequences if such requirement is not obliged with. This paper also seeks to provide better comprehension of the existence of section 34 and section 47, in line with the objective of this study. The article entitled 'Married or not married- That is the question' written by Balwant Singh Sidhu has critically discussed and commented on the problems arising of the confusing proper interpretation of Section 34. A number of materials consisting of books by various authors from Malaysia and United Kingdom, had been referred as guide to resolve the issues of this study. All the information and findings resulted by the study were attentively organized into smaller topics, which focused on the issues of importance of registration of marriage and the legal effects of noncompliance with such requirement. Accordingly, from the studies conducted, it was observed that section 34 of the Law Reform (Marriage & Divorce) Act 1976 has two different consequences, section 47, on the other hand, functions as a tool in helping the local courts in attending various cases and the issue of claiming for maintenance, inheritance and division of property when it comes to the situation resulting from an unregistered marriage, the claims are much more complicated and sometimes, will not be granted by the court. Thus, it can be concluded that registration of marriages is fundamental and the Law Reform (Marriage & Divorce) Act 1976 is very clear in showing its real intention to provide for a monogamous marriage through the requirement of registration of marriage.